Problem tożsamości i samoidentyfikacji politycznej mieszkańców terenów okupowanych we wschodniej Ukrainie (w latach 2014 – 2020) .......... 263 (Tożsamość i pamięć : konteksty kulturowe i społeczne. Studia ukrainoznawcze, 2021)
THE PROBLEM OF POLITICAL IDENTITY AND SELF-IDENTIFICATION OF THE INHABITANTS OF THE OCCUPIED TERRITORIES IN EASTERN UKRAINE (IN THE YEARS 2014-2020) In this article, the author analyzes the issue of political identity and self-identification of the inhabitants of the occupied territories in eastern Ukraine. Based on the results of sociological research carried out in Donbas in 2014-2020, the author describes the worldview and attitudes of people who live in unrecognized “republics” in the Donetsk and Lugansk regions. The views, opinions, the vision of the world and political self-identification of people living in regions occupied by separatists are intensively shaped by Russian propaganda, local media and the “republican” education system. The analysis shows that in the occupied territories a new regional identity is being created. The new identity that distinguishes the inhabitants of Donbas is to confirm that a given region is unique in the entire post-Soviet area, which implicitly means that it has special rights and privileges, also of a political nature. As a result, anti-Ukrainian and anti-Western views dominate among the inhabitants of areas not controlled by Kyiv, most of their inhabitants would like to join Russia and do not see their future within Ukraine. This calls into question Kyiv’s plans to reintegrate the occupied territories in the Donetsk and Luhansk Oblasts.